Genipin-Cross-Linked Silk Fibroin/Alginate Dialdehyde Hydrogel with Tunable Gelation Kinetics, Degradability, and Mechanical Properties: A Potential Candidate for Tissue Regeneration - Vaziri, Asmasadat; Vasheghani-Farahani, Ebrahim; Hosseinzadeh, Simzar; Bagheri, Fatemeh; Büchner, Margitta; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomacromolecules, 2024)
Genipin-cross-linked silk fibroin (SF) hydrogel is considered to be biocompatible and mechanically robust. However, its use remains a challenge for in situ forming applications due to its prolonged gelation process. In our attempt to facilitate the in situ fabrication of a genipin-mediated SF hydrogel, alginate dialdehyde (ADA) was utilized as a reinforcement template. Here, SF/ADA-based hydrogels with different compositions were synthesized covalently and ionically. Incorporating ADA into the SF hydrogel increased pore size (44.66-174.66 μm), porosity (61.59-80.40%), and the equilibrium swelling degree (7.60-30.17). Moreover, a wide range of storage modulus and compressive modulus were obtained by adjusting the proportions of SF and ADA networks within the hydrogel. The in vitro cell analysis using preosteoblast cells (MC3T3-E1) demonstrated the cytocompatibility of all hydrogels. Overall, the covalently and ionically cross-linked SF/ADA hydrogel represents a promising solution for in situ forming hydrogels for applications in tissue regeneration.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Biopolymers; Gelation; Hydrogels; Nucleic acid structure; Peptides and proteins